Magnesium battery electrolyte containing insoluble additive and application thereof
By adding anhydrous insoluble indium additives to the magnesium battery electrolyte, the problem that magnesium batteries are difficult to dissolve additives under water and oxygen-free conditions is solved, and a magnesium battery electrolyte with low internal resistance, high performance and long cycle life is achieved.
Patent Information
- Application Number
- CN202411807013.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-02-28
AI Technical Summary
Magnesium batteries are difficult to dissolve insoluble additives under water and oxygen-free conditions. The existing technology is complex and cannot ensure the complete removal of moisture in the electrolyte, resulting in insufficient battery performance and cycle life.
Add anhydrous insoluble indium additives, such as In2O3 nanoparticles and In2(SO4)3 nanoparticles, to the water-free magnesium electrolyte, and prepare the electrolyte by stirring evenly to avoid high temperature and water removal treatment, and the process is simple and easy to industrially produce.
It realizes the promotion of magnesium ion conduction under water and oxygen-free conditions, reduces the internal resistance of the battery, improves the battery performance and cycle life, and the process is simple and does not require a large amount of co-solvents.
Smart Images

Figure HDA0005179523530000011 
Figure HDA0005179523530000012 
Figure HDA0005179523530000021
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electrolytes, and in particular to a magnesium battery electrolyte containing an insoluble additive, and a preparation method and application thereof. Background Art
[0002] Adding additives to magnesium battery electrolyte is one of the important means to improve the performance of magnesium batteries. However, the magnesium negative electrode is very sensitive to moisture and oxygen, and most electrolyte additives face the problem of being difficult to dissolve under water-free and oxygen-free conditions. The existing technology generally eliminates the adverse effects of moisture and oxygen on the magnesium negative electrode interface by first dissolving additives containing crystal water and then dehydrating the system or adding a large amount of co-solvents to the electrolyte to promote the dissolution of anhydrous additives, thereby improving the performance of the battery.
[0003] Chinese patent CN 115954549A "A magnesium battery electrolyte, preparation method and magnesium battery" uses a method of dissolving water-containing additives first and then removing water from the system. First, the magnesium salt is subjected to high-temperature vacuum drying, and then the treated magnesium salt and solid additives, organic boric acid and its derivatives, and liquid additives are dissolved in an ether organic solvent. Then, a 3A molecular sieve activated at 300°C for 5h is used to remove water from the electrolyte system, which effectively improves the ionic conductivity and accelerates the battery's kinetic process. However, the high-temperature treatment process may cause the loss of effective ingredients in the electrolyte, and the method is complex and cannot ensure complete removal of water from the electrolyte.
[0004] Chinese patent CN 113258138A "An all-inorganic salt type rechargeable magnesium battery electrolyte and its preparation method" uses a method of adding a cosolvent to the electrolyte to promote the dissolution of anhydrous magnesium salt. A chlorine-containing cosolvent is added to the electrolyte to form a complex with the solvent, which significantly improves the solubility of the electrolyte magnesium salt in the organic solvent and the conductivity of the electrolyte, and reduces the overpotential. It can be seen that adding a cosolvent to the electrolyte can promote the dissolution of anhydrous magnesium salt. However, the addition of a large amount of cosolvent increases the concentration of the electrolyte system and the viscosity is high, which is not conducive to ion transmission and has an extremely adverse effect on the long-term cycle of the battery.
[0005] In order to avoid the problem of additives being difficult to dissolve and the adverse effects of additives after dissolution, some researchers have proposed adding insoluble additives directly to the electrolyte to explore their performance. Chinese patent CN 201610540821.3 "An electrolyte containing inorganic additives and a lithium-ion battery containing the electrolyte" adds insoluble additives such as aluminum oxide and silicon oxide to the lithium battery electrolyte as a water absorbent to absorb moisture in the battery and neutralize harmful gases, thereby extending the battery life; Chinese patent CN 200910036874.1 "An additive for a liquid electrolyte of a lithium-ion battery and the resulting electrolyte" adds nano-scale inorganic oxide additives to the lithium-ion battery electrolyte as a flame retardant to improve the safety performance of the lithium battery; Chinese patent CN 200580040944.0 "Non-aqueous electrolyte battery" disperses or dissolves indium compounds in the electrolyte, and undergoes a replacement reaction with lithium, thereby forming an indium-containing protective film to inhibit excessive reaction between lithium and the electrolyte.
[0006] The electrolyte prepared by the above invention has a simple process, and the insoluble additives do not need to be dissolved, and the viscosity of the electrolyte will not increase due to the presence of the co-solvent. Therefore, the internal resistance of the battery is low, and it performs well in long-term cycle performance. The principle of this type of invention is essentially to protect the lithium negative electrode by adding insoluble additives to the electrolyte to improve the cycle life and safety performance of the lithium battery. The problems that magnesium batteries need to solve are different from those of lithium batteries. Magnesium is not easy to produce dendrites and has excellent safety performance, but it is easy to react with air or water to form a passivation film. This passivation film is different from the protective film required for lithium batteries and is extremely unfavorable for the conduction of magnesium ions. Therefore, it is urgent to develop a magnesium battery electrolyte with a simple preparation process, low viscosity, and can effectively promote the conduction of magnesium ions under anhydrous and oxygen-free conditions. Summary of the invention
[0007] Based on the problems existing in the prior art, the present invention designs a high-performance magnesium battery electrolyte containing an insoluble additive. By adding anhydrous insoluble indium additives to a non-aqueous magnesium electrolyte, the preparation is completed after stirring, without the need for high temperature and water removal treatment, the process is very simple, and it is easy to carry out large-scale industrial production; and the insoluble additive can play a good role in the electrolyte without being dissolved, avoiding the large-scale use of co-solvents, and the obtained magnesium electrolyte has low viscosity and high main salt utilization, thereby reducing the internal resistance of the battery and improving the performance and cycle life of the battery.
[0008] The present invention provides the following technical solutions:
[0009] A magnesium battery electrolyte containing an insoluble additive is prepared by uniformly dispersing indium-containing nanoparticles and a magnesium salt electrolyte in an organic solvent after adding a suspension stabilizer;
[0010] Wherein, the magnesium battery is a composite of one or more of a magnesium ion battery, a magnesium oxygen battery, and a magnesium sulfur battery;
[0011] The magnesium salt electrolyte is a composite of one or more of magnesium bis(trifluoromethanesulfonyl)imide, magnesium bis(hexamethyldisilazide), magnesium sulfate and magnesium carbonate;
[0012] The organic solvent is one or a mixture of two of dimethyl ether, tetraethylene glycol dimethyl ether, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethylene glycol dimethyl ether, N,N-dimethylformamide, dimethyl sulfoxide, ethyl methyl carbonate, polycarbonate, tetrahydrofuran, 1,3-dioxolane, and trimethyl phosphate;
[0013] The indium-containing nanoparticles are a composite of one or more of elemental indium, trivalent indium ion salts and divalent indium ion salts, preferably a composite of one or two of indium trioxide nanoparticles and indium sulfate (In2(SO4)3) nanoparticles;
[0014] The indium-containing nanoparticles have a particle size range of 1-100 nm. If the particle size exceeds 100 nm, the effect of fixing anions in the electrolyte by the nanoparticles cannot be achieved.
[0015] The indium-containing nanoparticles are dispersed in the organic solvent in one or more of a nanoparticle suspension and a colloidal particle solvation dispersion;
[0016] The amount of indium-containing substance added is 1-5wt.% of the matrix electrolyte;
[0017] The suspension stabilizer is one or more of polyethylene glycol diacrylate, Tween, sodium carboxymethyl cellulose, sodium polyacrylate, and polyamide, and the amount used is 1-10wt.% of the matrix electrolyte;
[0018] The beneficial effect of the present invention is that by adding insoluble indium additives such as In2O3 nanoparticles, In2(SO4)3 nanoparticles and nano-In powder to the electrolyte, the non-functionalized sites on the nanoparticle core interact with the anions in the magnesium electrolyte to produce a synergistic effect, thereby fixing the anions in the electrolyte and improving the Mg 2+ The migration number and ion utilization rate accelerate the transmission of magnesium ions.
[0019] The magnesium battery electrolyte containing the insoluble additive provided by the present invention does not need to be dehydrated, the process is very simple, and it is easy to be industrially produced on a large scale; the insoluble additive can play a good role in the electrolyte without being dissolved, avoiding the large-scale use of co-solvents, and obtaining an electrolyte with low viscosity and high main salt utilization rate, thereby reducing the internal resistance of the battery, thereby improving the performance and cycle life of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 The first cycle charge and discharge curves of the magnesium battery assembled with the electrolyte prepared in Example 1 and Comparative Example 1 at 0.05C;
[0021] Figure 2 Comparison of electrochemical performance of the electrolyte prepared in Example 3 and the magnesium ion battery assembled by adding different additives;
[0022] Figure 3 Comparison of the coulombic efficiency of the magnesium oxygen battery assembled with the electrolyte prepared in Example 2 and Comparative Example 1 in the first 50 cycles;
[0023] Figure 4 Electrochemical impedance spectra of magnesium-sulfur batteries assembled with electrolytes prepared in Example 1 and Comparative Examples 1 and 2. DETAILED DESCRIPTION
[0024] The present invention is further described below in conjunction with specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.
[0025] Example 1
[0026] Preparation of single-element indium nanoparticle suspension electrolyte and assembly of magnesium-sulfur battery
[0027] In a circulating purification glove box with a water content and an oxygen content both lower than 0.1 ppm, 1.5 g of bis(trifluoromethylsulfonyl imide) magnesium powder and 0.1 g of elemental indium nanoparticles (nanoscale) were weighed, tetraethylene glycol dimethyl ether was added, and 0.5 g of polyethylene glycol diacrylate was added as a suspension stabilizer to make the total mass of the electrolyte 10 g. The electrolyte was ultrasonicated for 12 h in the circulating purification glove box, and after standing for 12 h, an elemental indium nanoparticle suspension electrolyte (elemental indium content of 1 wt.%) was obtained.
[0028] A magnesium-sulfur battery was assembled with magnesium metal as the negative electrode, sulfur-carbon composite material as the positive electrode, PP / PE composite porous membrane as the separator, and the above-obtained electrolyte. The first cycle specific capacity of the sulfur-carbon positive electrode was 602 mAh g at a rate of 0.05C. -1 , the capacity retention rate after 100 cycles is 68%.
[0029] Comparative Example 1
[0030] Preparation of magnesium-sulfur batteries
[0031] In a circulating purification glove box with water and oxygen contents below 0.1 ppm, 1.5 g of bis(trifluoromethylsulfonyl imide) magnesium powder was weighed and tetraethylene glycol dimethyl ether was added to the total mass of the electrolyte to 10 g without adding any additives. The battery assembly method was the same as in Example 1. The first cycle specific capacity of the sulfur-carbon positive electrode at a rate of 0.05C was 385 mAh g -1, the capacity retention rate after 100 cycles is 61%.
[0032] The magnesium-sulfur battery was assembled in the same manner as in Example 1.
[0033] Figure 1 The first cycle charge and discharge curves at 0.05C for the magnesium battery assembled with the electrolyte prepared in Example 1 and Comparative Example 1 show that the capacity of the magnesium-sulfur battery assembled with the suspended electrolyte containing elemental indium nanoparticles is greatly improved at a relatively high charge and discharge rate, the discharge voltage platform is increased to nearly 1.25V, and the voltage range is significantly expanded.
[0034] Comparative Example 2
[0035] Preparation of magnesium-sulfur batteries
[0036] In a circulating purification glove box with a water content and an oxygen content both lower than 0.1 ppm, 1.5 g of bis(trifluoromethylsulfonyl imide) magnesium powder and 0.1 g of a soluble additive InCl3 were weighed, and tetraethylene glycol dimethyl ether was added to a total mass of the electrolyte of 10 g. The battery assembly method was the same as in Example 1. The electrolyte viscosity was high and the battery internal resistance was large.
[0037] Figure 4 From the electrochemical impedance spectra of magnesium-sulfur batteries assembled with the electrolytes prepared in Example 1 and Comparative Examples 1 and 2, it can be seen that the internal resistance of the battery assembled using the low-viscosity electrolyte prepared in Example 1 is about 50Ω, which is much lower than that of the other two high-viscosity electrolytes.
[0038] Example 2
[0039] Preparation of magnesium oxygen battery
[0040] Take 9.4 g of Mg(TFSI)2 / DME electrolyte with a concentration of 0.5M, add 0.1 g of indium trioxide nanoparticles (nanoscale), and add 0.5 g of polyethylene glycol diacrylate as a suspension stabilizer, stir evenly, and prepare an indium oxide nanoparticle suspension electrolyte (indium oxide content is 1 wt.%).
[0041] Using metallic magnesium as the negative electrode, magnesium peroxide as the positive electrode, and a PP / PE composite porous membrane as the separator, the indium oxide nanoparticles prepared above were suspended in the electrolyte, and a magnesium oxygen battery was prepared by conventional methods. The obtained battery had a first discharge time of 3000 min at a rate of 0.05C, which was more than 3 times higher than the battery cycle performance of a battery without indium oxide nanoparticles added to the electrolyte.
[0042] Figure 3 Comparison of the coulombic efficiencies of the magnesium oxygen batteries assembled with the electrolytes prepared in Example 2 and Comparative Example 1 during the first 50 cycles shows that the battery obtained in Example 2 has a cycle performance more than three times higher than that of the battery without indium oxide nanoparticles added to the electrolyte.
[0043] Example 3
[0044] Preparation of magnesium ion batteries
[0045] 0.2g of indium sulfate (nanoscale) was mixed with 1.6g of tetraethylene glycol dimethyl ether (TGDE), ball milled for 2h, and 0.2g of Tween was added to obtain a dispersion. 1g of the above dispersion was mixed with 9g of 1M Mg(ClO4)2 / TGDE electrolyte to obtain an electrolyte with solvated colloidal particles dispersed therein (indium sulfate content of 1wt.%).
[0046] The battery was assembled with MgFeSiO4 as the positive electrode, magnesium metal as the negative electrode, and PP / PE composite porous membrane as the separator, and the above electrolyte was used to assemble the battery. The specific capacity of the positive electrode of the obtained battery can reach 309 mAh g -1 Compared with the sample without indium sulfate, the overpotential is 55mV lower and the capacity retention rate after 100 cycles is about 68%, which is more than 3 times higher.
[0047] Figure 2 Comparison of the electrochemical performance of the electrolyte prepared in Example 3 and the magnesium ion battery assembled with different additives shows that the electrochemical performance of the electrolyte with indium trioxide nanoparticles and indium sulfate nanoparticles as additives is better than that of the single indium additive.
[0048] Example 4
[0049] Preparation of magnesium-sulfur batteries
[0050] In a circulating purification glove box with a water content and an oxygen content both lower than 0.1 ppm, 1.5 g of bis(trifluoromethylsulfonyl imide) magnesium powder and 0.24 g of elemental indium nanoparticles (nanoscale) were weighed, tetraethylene glycol dimethyl ether was added, and 0.5 g of polyethylene glycol diacrylate was added as a suspension stabilizer to make the total mass of the electrolyte 10 g. The electrolyte was ultrasonicated for 12 h in the circulating purification glove box, and then allowed to stand for 12 h to obtain an elemental indium nanoparticle suspension electrolyte (the elemental indium content was 2.4 wt.%).
[0051] The battery assembly method is the same as in Example 1. The first cycle specific capacity of the sulfur-carbon positive electrode at a rate of 0.05C is 582 mAh g -1 , the capacity retention rate after 100 cycles is 66%.
[0052] Example 5
[0053] Preparation of magnesium-sulfur batteries
[0054] In a circulating purification glove box with a water content and an oxygen content both lower than 0.1 ppm, 1.5 g of bis(trifluoromethylsulfonyl imide) magnesium powder and 0.48 g of elemental indium nanoparticles (nanoscale) were weighed, tetraethylene glycol dimethyl ether was added, and 0.5 g of polyethylene glycol diacrylate was added as a suspension stabilizer to make the total mass of the electrolyte 10 g. The electrolyte was ultrasonicated for 12 h in the circulating purification glove box, and after standing for 12 h, an elemental indium nanoparticle suspension electrolyte (elemental indium content of 4.8 wt.%) was obtained.
[0055] The battery assembly method is the same as in Example 1. The first cycle specific capacity of the sulfur-carbon positive electrode at a rate of 0.05C is 588 mAh g -1 , the capacity retention rate after 100 cycles is 67%.
[0056] Example 6
[0057] Preparation of magnesium ion batteries
[0058] 0.64g of indium sulfate (nanoscale) was mixed with 1.16g of tetraethylene glycol dimethyl ether (TGDE), ball milled for 2h, and 0.2g of Tween was added to obtain a dispersion. 1g of the above dispersion was mixed with 9g of 1M Mg(ClO4)2 / TGDE electrolyte to obtain an electrolyte with solvated colloidal particles dispersed therein (indium sulfate content of 3.2wt.%).
[0059] The battery assembly method is the same as in Example 3. The first cycle specific capacity of the sulfur-carbon cathode at a rate of 0.05C is 294 mAh g -1 , compared with the sample without indium sulfate, the overpotential is 53mV lower, and the capacity retention rate after 100 cycles is about 68%.
[0060] Comparative Example 3
[0061] Preparation of silicon oxide nanoparticle suspension electrolyte and assembly of magnesium-sulfur battery
[0062] In a circulating purification glove box with a water content and an oxygen content both lower than 0.1 ppm, 1.5 g of magnesium bistrifluoromethanesulfonyl imide powder and 0.1 g of silicon oxide nanoparticles (nanoscale) were weighed and added to tetraethylene glycol dimethyl ether, and 0.5 g of polyethylene glycol diacrylate was added as a suspension stabilizer so that the total mass of the electrolyte was 10 g, to prepare a silicon oxide nanoparticle suspension electrolyte.
[0063] The assembled magnesium-sulfur battery has a first-cycle specific capacity of 390 mAh g at a rate of 0.05C. -1 , the capacity retention rate after 100 cycles is 59%.
[0064] Comparative Example 4
[0065] Preparation of aluminum oxide nanoparticle suspension electrolyte and assembly of magnesium-sulfur battery
[0066] In a circulating purification glove box with a water content and an oxygen content both lower than 0.1 ppm, 1.5 g of magnesium bistrifluoromethanesulfonyl imide powder and 0.1 g of alumina nanoparticles (nanoscale) were weighed and added to tetraethylene glycol dimethyl ether, and 0.5 g of polyethylene glycol diacrylate was added as a suspension stabilizer to make the total mass of the electrolyte 10 g to prepare an alumina nanoparticle suspension electrolyte.
[0067] The assembled magnesium-sulfur battery has a first-cycle specific capacity of 375 mAh g at a rate of 0.05C. -1 , the capacity retention rate after 100 cycles is 61%.
[0068] Comparative Example 5
[0069] Preparation of calcium carbonate nanoparticle suspension electrolyte and assembly of magnesium ion battery
[0070] Take 0.2g of calcium carbonate (nanoscale) and mix it with 1.6g of TGDE and add 0.2g of Tween and then ball mill for 2h. Take 1g of the above dispersion and mix it evenly with 9g of 1M Mg(ClO4)2 / TGDE electrolyte to obtain an electrolyte dispersed with solvated colloidal particles. With MgFeSiO4 as the positive electrode, magnesium metal as the negative electrode, and PP / PE composite porous membrane as the separator, the battery positive electrode specific capacity assembled with the above electrolyte is about 214mAh g -1 , which is far lower than the theoretical specific capacity of MgFeSiO4 positive electrode.
[0071] Comparative Example 6
[0072] Preparation of zinc oxide nanoparticle suspension electrolyte and assembly of magnesium oxygen battery
[0073] Take 9.4 g of Mg(TFSI)2 / DME electrolyte with a concentration of 0.5 M, add zinc oxide nanoparticles (nanoscale), and add 0.5 g of polyethylene glycol diacrylate as a suspension stabilizer, stir evenly, and prepare a zinc oxide nanoparticle suspension electrolyte.
[0074] The battery assembly method is the same as in Example 2. The first discharge time of the obtained battery at a rate of 0.05C is about 1400 min.
[0075] The above-described embodiments are only preferred embodiments for fully illustrating the present invention, and the protection scope of the present invention is not limited thereto. Equivalent substitutions or changes made by those skilled in the art based on the present invention are within the protection scope of the present invention, and the protection scope of the present invention shall be subject to the claims.
Claims
1. A magnesium battery electrolyte containing an insoluble additive, characterized in that: The indium-containing nanoparticles and magnesium salt electrolyte are uniformly dispersed in an organic solvent after adding a suspension stabilizer; the indium-containing nanoparticles are a composite of one or more of elemental indium, insoluble trivalent indium ion salt and insoluble divalent indium ion salt.
2. The magnesium battery electrolyte containing an insoluble additive as claimed in claim 1, characterized in that: The magnesium salt electrolyte is a composite of one or more of magnesium bis(trifluoromethanesulfonyl)imide, magnesium bis(hexamethyldisilazide), magnesium sulfate and magnesium carbonate.
3. The magnesium battery electrolyte containing an insoluble additive as claimed in claim 1, characterized in that: The organic solvent is one or a mixture of two of dimethyl ether, tetraethylene glycol dimethyl ether, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethylene glycol dimethyl ether, N,N-dimethylformamide, dimethyl sulfoxide, ethyl methyl carbonate, polycarbonate, tetrahydrofuran, 1,3-dioxolane, and trimethyl phosphate.
4. The magnesium battery electrolyte containing an insoluble additive as claimed in claim 1, characterized in that: The insoluble trivalent indium ion salt is indium trioxide nanoparticles, and the insoluble divalent indium ion salt is indium sulfate nanoparticles.
5. The magnesium battery electrolyte containing an insoluble additive as claimed in claim 1, characterized in that: The indium-containing nanoparticles have a particle size range of 1-100 nm.
6. The magnesium battery electrolyte containing an insoluble additive as claimed in claim 1, wherein the additive containing indium nanoparticles is dispersed in the organic solvent in one or more of the following dispersion methods: nanoparticle suspension, colloidal particle solvation dispersion.
7. The magnesium battery electrolyte containing an insoluble additive as claimed in claim 1, characterized in that: The amount of indium-containing nanoparticles added is 1-5 wt.% of the electrolyte.
8. The magnesium battery electrolyte containing an insoluble additive as claimed in claim 1, characterized in that: The suspension stabilizer is one or more of polyethylene glycol diacrylate, Tween, sodium carboxymethyl cellulose, sodium polyacrylate, and polyamide, and the amount used is 1-10wt.% of the electrolyte.
9. Use of the magnesium battery electrolyte containing an insoluble additive as claimed in any one of claims 1 to 8 in a magnesium battery, characterized in that: The magnesium battery is a combination of one or more of a magnesium ion battery, a magnesium oxygen battery, and a magnesium sulfur battery.
Citation Information
Patent Citations
Battery with nonaqueous electrolyte
CN100499228C
Additive of lithium ion battery liquid electrolyte and obtained electrolyte
CN101783421A
Electrolyte containing inorganic additive and lithium-ion battery containing electrolyte
CN105938919A
Full inorganic salt type rechargeable magnesium battery electrolyte and preparation method thereof
CN113258138A
Magnesium battery electrolyte, preparation method and magnesium battery
CN115954549A
Cited By
Inorganic magnesium salt electrolyte for rechargeable magnesium battery as well as preparation method and application of inorganic magnesium salt electrolyte
CN119905658A
Halogen-free single-solvent rechargeable magnesium battery electrolyte and preparation method and application thereof
CN120709509A
Magnesium secondary battery electrolyte and preparation method thereof
CN120767411A
Magnesium secondary battery electrolyte and preparation method thereof
CN120767411B